pH and Sugar Content of Honey Pineapple Jam (Ananas comosus L Merr) with Addition of Carrageenan - Ajeng Zahra Kinanti; Nurwati; Muhamad Hasdar (Universitas Veteran Bangun Nusantara, 2023)
This study aims to evaluate the effect of adding carrageenan to the pH value and sugar content of honey pineapple jam. Honey pineapple (Ananas comosus L. Merr) was used as the main ingredient with the addition of carrageenan at concentrations of 0%, 0.2%, 0.6%, and 1%. The method used is a completely randomized design (CRD) with one factor and three replications. The results showed that the addition of carrageenan significantly (P<0.05) affected the sugar content in pineapple jam. The higher the carrageenan concentration, the lower the sugar content in pineapple jam. However, the addition of carrageenan had no significant effect (P>0.05) on the pH of pineapple jam. Carrageenan acts as a thickener and water binder in jam but does not substantially change the level of acidity (pH). Keywords: carrageenan, sugar content, honey pineapple jam, and pH